The extent of charitable organisations’ disclosures of information and its relationship with donations / Ruhaya Atan, Saunah Zainon and Yap Bee Wah. - Atan, Ruhaya; Zainon, Saunah; Yap, bee Wah (Universiti Teknologi MARA Cawangan Selangor, 2012)
This study examines the extent of disclosures of information by charitable organisations and the effect of total donations on disclosure. The sample of this study consists of annual returns for the financial year 2009 of 101 charitable organisations. The disclosure score obtained was based on the ratio of total disclosure score to its total possible disclosure score. The overall total disclosures are very low and below the mean score. Statistical results indicate that the extent of disclosure is significantly related to total donations received. This study provides evidence to the management of the charitable organisations in Malaysia to improve their financial disclosure of information in their reporting so as to convince the stakeholders that the resources are used efficiently for charitable services. Due to the unique features of charitable organisations, ChORI was developed and applied in this study to assist in the examination of the extent of disclosures of information.